Low pathogenicity of anti‐desmoglein 3 immunoglobulin G autoantibodies contributes to the atypical clinical phenotypes in pemphigus. Issue 7 (24th April 2015) - Saleh, Marwah A.; Hashimoto, Rena; Kase, Yuko; Amagai, Masayuki; Yamagami, Jun
Abstract The clinical phenotypes of pemphigus can be explained by the desmoglein (Dsg) compensation theory. However, some atypical cases such as cutaneous pemphigus vulgaris (cPV), in which patients have anti‐Dsg3 antibodies without oral erosions, do not conform to this theory. To explain the discrepancy between clinical phenotypes and anti‐Dsg antibody profiles, the pathogenic strength of immunoglobulin (Ig)G autoantibodies against Dsg3 must be taken into consideration. We analyzed the epitopes and blister‐inducing pathogenic strength of the sera from three patients having IgG against Dsg3 without oral erosions with domain‐swapped recombinant proteins and dissociation assay using cultured normal human epidermal keratinocytes. The results showed that all sera contained IgG directed against the amino terminal EC1 domain of Dsg3, as is found in most PV sera. However, dissociation assays revealed that the pathogenic strength of the anti‐Dsg3 antibodies in all three cases was extremely lower than that of typical PV cases with mucosal involvement. In conclusion, when anti‐Dsg3 IgG antibodies are not sufficient to inhibit the expression of Dsg3 in the oral mucosa, but can inhibit the expression in the skin, skin blisters can result. Therefore, the pathogenicity of anti‐Dsg3 antibodies should be regarded as a key factor contributing to the clinical phenotype in pemphigus patients with conflicting antibody profiles.